Confessions of an ugly stepsister - Maguire, Gregory (New York, N.Y. : Regan Books, 2000)
On seeing her portrait, a servant girl modelling for an artist in 17th century Holland realizes she is ugly. But the portrait opens her eyes to the world of art, she becomes a painter and is transformed by her work so that when a prince charming appears she is no longer ugly.
860
Accelerated Reader AR
Keywords: Beauty, Personal -- Fiction; Fairy tales -- Adaptation; Stepsisters -- Fiction; Haarlem (Netherlands) -- Fiction; Historical fiction